Dynamics of CG during acceleration of maximal sprint - Nagahara, R.; Matsuo, A.; Matsubayashi, T.; Zushi, K. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Running speed of maximal sprint is usually approximated by exponential equation (Chelly and Denis, 2001; Volkov and Lapin, 1979). This approximation is based on the idea which the acceleration of sprinters gradually becomes small. On the other hand, it is generally thought that the height of whole body centre of gravity (CG) during acceleration of maximal sprint becomes high with increasing running speed. However, a previous study showed that the increasing running speed during maximal sprint changed like a cubic curve (Nagahara, 2009). Moreover, in practical side, the acceleration of maximal sprint is divided into two or three sections. Thus, the purpose of this study was to clarify whether the running speed and height of CG during acceleration of maximal sprint gradually increase or not. Methods: Twelve male sprinters (age 21.6 ± 2.6 yr, stature 1.74 ± 0.04 m, body mass 68.1 ± 4.1 kg and the best time of 100 m race 10.71 ± 0.33 s) participated in this study. The subjects performed 60 m sprint twice with maximal effort started by crouch position as used in 100 m race. The time of 60 m sprint was measured using photocell connected starting gun and VICON motion-capture system. Whole running motion from start to 50 m mark was recorded using VICON system consisted by sixty cameras (250Hz). The coordinates of segment endpoints were obtained by filtering and CG were calculated. Results and Discussion: Time of 60 m sprint was 7.24 ± 0.16 s. As a typical result, the height of CG increased to the 11th step, and then leveled off to the 18th step, and gradually decreased thereafter while the running speed still increased. At the same spot, the 11th step, the acceleration shifted to constant and decreased again thereafter. These are novel and unexpected results and suggest that the sprinters accelerate with unsteady change of running speed and height of CG.